Technique to interconnect and control co‐simulation systems. Issue 12 (21st June 2017) - Broderick, Stephen; Cruden, Andrew; Sharkh, Suleiman; Bessant, Nigel
Abstract : A 'Run Time Scheduler' (RunTS) is presented, a minimalist Discrete Event Simulator able to sequence the operation of multiple simulators, coordinating a simulation of several elements so to form a whole system. Dynamic cause‐effect chains may emerge. In operation the net simulation possesses a known steady‐state other than when changed. RunTS controls the application of state‐changes, passing these to specific simulators to determine new steady‐states. Messages can pass between simulations concerning configuration data, commands and results. Simulators must meet connectability criteria. The method allows variable periods between simulation stages rather than a fixed tempo, and can undertake specific simulation sequences unique to each event, through use of a novel per‐event state‐machine. RunTS is part of INSim, a Smart Grid simulator working with a mix of components including Electric Vehicles, Smart Agents and OpenDSS, a power network analysis tool.